Womb city - Tsamaase, Tlotlo (Erewhon, an imprint of Kensington Publishing Corp., 2024)
This genre-bending Africanfuturist horror novel blends The Handmaid's Tale with Get Out in an adrenaline-packed, cyberpunk body-hopping ghost story exploring motherhood, memory, and a woman's right to her own body. Nelah seems to have it all: fame, wealth, and a long-awaited daughter growing in a government lab. But, trapped in a loveless marriage to a policeman who uses a microchip to monitor her every move, Nelah's perfect life is precarious. After a drug-fueled evening culminates in an eerie car accident, Nelah commits a desperate crime and buries the body, daring to hope that she can keep one last secret. The truth claws its way into Nelah's life from the grave. As the ghost of her victim viciously hunts down the people Nelah holds dear, she is thrust into a race against the clock: in order to save any of her remaining loved ones, Nelah must unravel the political conspiracy her victim was on the verge of exposing--or risk losing everyone. Set in a cruel futuristic surveillance state where bodies are a government-issued resource, this harrowing story is a twisty, nail-biting commentary on power, monstrosity, and bodily autonomy. In sickeningly evocative prose, Womb City interrogates how patriarchy pits women against each other as unwitting collaborators in their own oppression. In this devastatingly timely debut novel, acclaimed short fiction writer Tlotlo Tsamaase brings a searing intelligence and Botswana's cultural sensibility to the question: just how far must a woman go to bring the whole system crashing down?